Planning for succession at boston construction group - a family-owned business - Hilgarth, Anna Beate (2022)
The succession process is one of the biggest challenges facing family businesses. An increasing number of family firms choose to select a non-family CEO as a successor for various reasons. This work projects investigates the case of a German family firm and its process of succession planning. If the ownership group of a family business wants to retain the company, it is crucial to have a common vision for the future. Thus, this study focuses on developing a shared vision of the family owners for the business, and subsequently lays outa roadmap for the company’s leadership transition to a non-family CEO. These results serve as an example for other family businesses, to stay on the right track to manage continuity.